Accompaniment in Understanding Religious Moderation at the Qur'an Education Communication Forum in Bandar Lampung City - Gandhi Liyorba Indra; M. Yasin al Arif; Ida Faridatul Hasanah (Smart Society, 2026)
Strengthening religious moderation has become an urgent necessity to prevent conflicts arising from radicalism and intolerance, particularly in non-formal religious education institutions such as Qur’anic Education Centers (TPQ). This community service program aims to enhance the understanding of religious moderation among Qur’an teachers who are members of the Qur’anic Education Communication Forum (FKPQ) in Bandar Lampung City, Indonesia, as an effort to instill moderation values in students from an early age. The study employed a Participatory Action Research (PAR) approach using Focus Group Discussions (FGDs) and questionnaires as the primary instruments. A total of 30 TPQ teachers participated in the program through three stages: preliminary assessment (pre-test), mentoring and training sessions covering religious moderation, radicalism, intolerance, and implementation strategies, followed by evaluation (post-test). The results demonstrated a significant improvement in participants’ understanding, with the average score increasing from 53 in the pre-test to 95 in the post-test. These findings indicate that the religious moderation assistance program effectively strengthened teachers’ understanding, which was subsequently transferred to students to support the development of a moderate Qur’anic learner generation. This program contributes by offering an applicable PAR-based model for strengthening religious moderation in non-formal Qur’anic education settings and may serve as a reference for policymakers and educational institutions in designing systematic and sustainable grassroots-level religious moderation programs.